2018
DOI: 10.1093/intimm/dxy004
|View full text |Cite
|
Sign up to set email alerts
|

Host immune responses toToxoplasma gondii

Abstract: Toxoplasma gondii can infect homoeothermic animals including humans and cause lethal toxoplasmosis in immunocompromised individuals. When hosts are infected with T. gondii, the cells induce immune responses against T. gondii. The pathogen infection is recognized by immune sensors that directly detect T. gondii structural components, leading to production of pro-inflammatory cytokines and chemokines. Antigen-presenting cells such as macrophages and dendritic cells strongly activate T cells and induce developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
120
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(128 citation statements)
references
References 90 publications
5
120
1
2
Order By: Relevance
“…Conversely, the transcriptomes from infected miceboth Bystander and TINs-showed evidence for moderate-to-high levels of T cell-, monocyte-, and macrophage-specific transcripts. These data are consistent with prior evidence that, during CNS infection with T. gondii, these cell types infiltrate into the CNS and significantly contribute to the control of CNS toxoplasmosis 41,42,10,[43][44][45][46][47] . Consistent with TINs showing higher levels of immune pathways ( Fig.…”
Section: Bystanderssupporting
confidence: 92%
“…Conversely, the transcriptomes from infected miceboth Bystander and TINs-showed evidence for moderate-to-high levels of T cell-, monocyte-, and macrophage-specific transcripts. These data are consistent with prior evidence that, during CNS infection with T. gondii, these cell types infiltrate into the CNS and significantly contribute to the control of CNS toxoplasmosis 41,42,10,[43][44][45][46][47] . Consistent with TINs showing higher levels of immune pathways ( Fig.…”
Section: Bystanderssupporting
confidence: 92%
“…It has been well-established that T. gondii-mediated type I immunity requires DCs for host defense [25][26][27][28][29]. Work from our lab and others have demonstrated that DC-deficiency results in acute host susceptibility to T. gondii [26,30].…”
Section: T-bet Is Critical To Maintain Inflammatory Dcs During T Gonmentioning
confidence: 99%
“…Likewise, the apicomplexan parasite Toxoplasma gondii is also confronted with the challenge of crossing tissue compartments in the body : In order to be able to enter the brain from the vasculature, T. gondii needs to replicate in and lyse endothelial cells of the blood brain barrier .…”
Section: Invasion Barrier Function and Virulence Strategiesmentioning
confidence: 99%